Implikasi Yuridis Penerapan ESG (Environmental, Social, and Governance) pada Perusahaan Pertambangan - Rehulina Dwitanty Sitepu; Erliasna Keytri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study is motivated by the increasing negative impacts of mining activities on the environment and society, as well as the suboptimal regulation of Environmental, Social, and Governance (ESG) within the Indonesian legal system. The objective of this study is to analyze ESG implementation from a legal perspective and examine its juridical implications for mining companies. This research employs a qualitative method with a normative juridical approach through the analysis of laws, legal doctrines, and scholarly literature. Data collection is conducted through library research and analyzed descriptively using legal interpretation methods. The findings indicate that ESG represents a non-financial norm integrated with sustainable development principles within Indonesian law. ESG regulation remains fragmented across sectoral laws, leading to regulatory disharmony and legal uncertainty. The implementation of ESG in mining companies is still suboptimal, particularly in Environmental, Social, and Governance aspects. Furthermore, ESG encourages a shift from compliance-based to value-based regulation in corporate legal compliance. ESG also expands corporate legal responsibility and enhances Environmental and social protection. In conclusion, strengthening regulations and legal harmonization is necessary to establish ESG as a mandatory standard in the mining sector.